Constraints in the Utilization of Map and Globe Media in Geography Learning - Zahrawati B, Fawziah; Andriani, Andriani; Asrikayana, Asrikayana; Darma, Darma; Agustina, Agustina; Purwanto, Aslam Raja (MANDALIKA : Journal of Social Science, 2023)
Learning media is one component of the learning process used by teachers in the classroom. Students will understand learning more easily when using media compared to not. This study aims to examine the implementation of the use of map and globe media, the obstacles in using map and globe media in geography learning and the solutions to these obstacles. This research is a qualitative research conducted at UPT SMA Negeri 3 Parepare, South Sulawesi, Indonesia. Data collection techniques, including interviews, observation, and documentation. The data validity was obtained through triangulation of theories, methods, and sources. This study found that the use of map and globe media in geography learning can improve students’ understanding of regionalism, but there are some students who are still constrained in understanding the use of maps and globes. This relates to student learning styles. This obstacle is related to the availability of graphic media, teacher skills in utilizing instructional media, and teacher preparation in understanding each student’s learning style. To get out of these obstacles, a teacher is expected to have skills in choosing the right media and methods by considering the diversity of student learning styles and the learning facilities owned by the school.